Gustatory modulation of the responses of trigeminal subnucleus caudalis neurons to noxious stimulation of the tongue in rats - Boucher, Yves (Eur J Neurosci, 2013)
Certain tastants inhibit oral irritation by capsaicin, whereas anesthesia of the chorda tympani (CT) enhances oral capsaicin burn. We tested the hypothesis that tastants activate the CT to suppress responses of trigeminal subnucleus caudalis (Vc) neurons to noxious oral stimuli. In anesthetized rats, we recorded Vc unit responses to noxious electrical, chemical (pentanoic acid, 200 μm) and thermal (55 °C) stimulation of the tongue. Electrically evoked responses were significantly reduced by a tastant mix and individually applied NaCl, monosodium glutamate (MSG), and monopotassium glutamate. Sucrose, citric acid, quinine and water (control) had no effect. Pentanoic acid-evoked responses were similarly attenuated by NaCl and MSG, but not by other tastants. Responses to noxious heat were not affected by any tastant. Transection and/or anesthesia of the CT bilaterally affected neither Vc neuronal responses to electrical or pentanoic acid stimulation, nor the depressant effect of NaCl and MSG on electrically evoked responses. Calcium imaging showed that neither NaCl nor MSG directly excited any trigeminal ganglion cells or affected their responses to pentanoic acid. GABA also had no effect, arguing against peripheral effects of GABA, NaCl or MSG on lingual nocicepive nerve endings. The data also rule out a central mechanism, as the effects of NaCl and MSG were intact following CT transection. We speculate that the effect is mediated peripherally by the release from taste receptor cells (type III) of some mediator(s) other than GABA to indirectly inhibit trigeminal nociceptors. The results also indicate that the CT does not exert a tonic inhibitory effect on nociceptive Vc neurons.